1989
DOI: 10.1093/protein/2.5.329
|View full text |Cite
|
Sign up to set email alerts
|

Polarity as a criterion in protein design

Abstract: Hypothetical proteins can be tested computationally by determining whether or not the designed sequence-structure pair has the characteristics of a typical globular protein. We have developed such a test by deriving quantities with approximately constant value for all globular proteins, based on empirical analysis of the exposed and buried surfaces of 128 structurally known proteins. The characteristic quantities that best appear to segregate badly designed or deliberately misfolded proteins from their properl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 0 publications
0
47
0
Order By: Relevance
“…In the present study, the effective charged surface area is introduced as a new concept similar to the one described by Baumann et al (1989). It describes the effective electrostatic interaction of bordering surfaces and is calculated for every atom by the point charge of an atom, multiplied by the surface area associated with the atom.…”
Section: Effective Charged Surface Areamentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the effective charged surface area is introduced as a new concept similar to the one described by Baumann et al (1989). It describes the effective electrostatic interaction of bordering surfaces and is calculated for every atom by the point charge of an atom, multiplied by the surface area associated with the atom.…”
Section: Effective Charged Surface Areamentioning
confidence: 99%
“…The most significant ones are (1) the ratio of the solvent-accessible surfaces of apolar and polar side chains, (2) empirical free energy functions, and (3) the number of buried charged atoms. Further studies including three-dimensional profile scores allow localization of differences between correctly and wrongly folded or mistraced structures without providing an unambiguous assessment (Baumann et al, 1989; Liithy et al, 1992).The correlation between the size of typical globular proteins and their respective surfaces has been proposed by Miller and coworkers (1987). More recent studies revealed that there is a strong correlation between the size of a protein and the solvation free energy of its folding (Chiche et al, 1990); this correlation should therefore be a useful criterion for the detection of incorrect model structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…O f these, the Ramachandran analysis of peptide dihedral angles (Ramachandran & Sasisekharan, 1968) was one of the first to classify allowed and nonallowed conformations; most grossly misfolded structures can be identified in this fashion. Several other methods that physiochemicallycharacterize a protein structure have been described, including the energetics methods of Novotny et al (1984), the atomic solvation parameter of Eisenberg and McLachlan (1986), and the evaluation of surface polarity (Baumann et al, 1989). Other empirical approaches include analysis of the pairwise likelihood of neighboring residues (Tanaka & Scheraga, 1976;Hendlich et al, 1990), the three-dimensional-one-dimensional profile method of Liithy et al (1992), and the fragment matching methods of Jones et al (1991).…”
mentioning
confidence: 99%
“…According to this model, the hydrophobic residues tend to be placed in the central part of the protein molecule and in hydrophilic residues on the protein's surface [38][39][40]. Even the recognition of native versus nonnative protein structures can be to some extent differentiated on the basis of spatial distribution of amino acid hydrophobicity [41][42][43]. The importance of hydrophobicity distribution has been emphasized, particularly for Rosetta development, when the description of the hydrophobic core significantly increased the performance of the Rosetta program [44].…”
Section: Introductionmentioning
confidence: 99%